OUTCOME BASE EDUCATION IMPLEMENTATION EDUCATION IN TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING: A CHALLENGE AND ISSUE - Nor Diyana Md Sin; Mohamad Zhafran Hussin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This paper explores the intricate process of implementing Outcome-Based Education (OBE) in Technical and Vocational Education and Training (TVET), with a focus on three primary themes. The text emphasises the significance and complexity of integrating OBE principles into TVET institutions, emphasising the need to synchronise educational philosophies with vocational training objectives. The second point focuses on identifying and analysing the challenges in aligning OBE with the particular objectives of TVET programmes. This encompasses variations in curriculum design, assessment techniques, and engagement of interested parties. The paper utilises a thorough examination of current literature in TVET. Anticipated results involve a thorough understanding of the barriers hindering effective OBE implementation in TVET, along with recommendations for overcoming these challenges. The study aims to provide tailored practical recommendations and optimal strategies for the TVET environment, ultimately helping to enhance educational quality and outcomes in vocational training. This paper aims to inform policymakers, educators, and stakeholders in the TVET sector to improve decision-making and implement OBE strategies in vocational education settings.